HYBRID COMPOSITES OF POLYPROPYLENE/RICE HUSK/TITANIUM DIOXIDE: THE EFFECTS OF COMPATIBILIZER ON THE MECHANICAL PROPERTIES AND MORPHOLOGY - Awang, M.; Wan Mohd, W.R.; Sarifuddin, N.; Tengku Ismail, T.N.S.; Harun, N. (Journal of Advanced Manufacturing Technology (JAMT), 2021)
The rising concern about plastic waste disposal has led to the research to overcome its related environmental problems. Indeed, blending of conventional plastic with degradable materials such as biomass from agro-waste byproduct has drawn a special attention to impart biodegradability. In this work, hybrid composites of polypropylene (PP) and rice husk (RH) containing different percentage of titanium dioxide (TiO2) (2wt% and 5 wt.%) with and without compatibilizer of maleic anhydride grafted polypropylene (MAPP) were prepared using injection molding method. The ratio of PP/RH and MAPP was fixed at 90/10 and 3 wt%, respectively. The main objective of the study was to analyze the effects of MAPP as a compatibilizer on the mechanical properties and morphology of the PP/RH/TiO2 composites. The results show that PP/RH/TiO2-5wt% with MAPP attained the highest results. An enhancement of about 20% and 11% in tensile strength and Young’s modulus, respectively was obtained with the inclusion of MAPP. The elongation at break, however, decreases with the inclusion of MAPP. Morphological examinations reveal that the presence of MAPP in hybrid composites improved compatibility between PP and RH leading to good interfacial adhesion.